On-Chip Group-IV Heisenberg-Limited Sagnac Interferometric Gyroscope at Room Temperature - Francesco De Leonardis; Richard Soref; Martino De Carlo; Vittorio M. N. Passaro (Sensors, 2020)
A room-temperature strip-guided “manufacturable” Silicon-on-Insulator (SOI)/GeSn integrated-photonics quantum-gyroscope chip operating at 1550 nm is proposed and analysed. We demonstrate how the entangled photons generated in Si Spontaneous Four Wave Mixing (SFWM) can be used to improve the resolution of a Sagnac interferometric gyroscope. We propose different integrated architectures based on degenerate and non-degenerate SFWM. The chip comprises several beam splitters, two SFWM entangled photon sources, a pump filter, integrated Mach–Zehnder interferometric gyro, and an array of waveguide coupled GeSn/Ge/Si single-photon avalanche detectors. The laser pumped SWFM sources generate the signal-idler pairs, which, in turn, are used to measure the two-photon, four-photon, and higher order coincidences, resulting in an increasing of the gyro resolution by a factor of two and four, with respect to the classical approach.